(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A new benthic foraminiferal species, Ellipsopolymorphina fragilis, observed in several deep—sea cores from the Eastern Mediterranean, is described for the first time. This species is typical and well represented in sediments deposited prior to or immediately after sapropels S—6 (185.000 a BP) and (225.000 a BP).
Keywords: Foraminifera; Benthos; New Species; Pleistocene; Mediterranean.